2017
DOI: 10.1007/s13149-017-0566-x
|View full text |Cite
|
Sign up to set email alerts
|

Maladie de Kaposi profuse chez un enfant VIH positif, probablement contaminé par sa grand-mère

Abstract: Kaposi's disease in children with HIV is rarely reported in everyday practice. This is a case study of cutaneous Kaposi's disease revealing HIV in a 5-year-old child with polymorphic eruption of papules and nodules on the face, trunk, back, and limbs. Histopathological examination confirmed the diagnosis of Kaposi's disease. The child's HIV serology was positive with a CD4 count of 240/mm, normochromic and normocytic anemia, and a hemoglobin level at 8.5 g/dl. It was found that the child, after early weaning f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The isolated cutaneous localization was observed in our patient in the form of hyperpigmented closets, erythematoangiomatous nodules and lymphedema. Dicko et al in Mali also reported a more extensive Kaposi skin disease revealing HIV in a child with a polymorphic rash of papules and nodules on the face, trunk, back and limbs [8] These same nodular lesions followed by purplish macules were reported by Karabinta et al [9]. Tounouga et al in Cameroon reported lesions mainly localized to the skin, and more rarely to the mucous membranes.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The isolated cutaneous localization was observed in our patient in the form of hyperpigmented closets, erythematoangiomatous nodules and lymphedema. Dicko et al in Mali also reported a more extensive Kaposi skin disease revealing HIV in a child with a polymorphic rash of papules and nodules on the face, trunk, back and limbs [8] These same nodular lesions followed by purplish macules were reported by Karabinta et al [9]. Tounouga et al in Cameroon reported lesions mainly localized to the skin, and more rarely to the mucous membranes.…”
Section: Discussionmentioning
confidence: 59%
“…Immunologically, only the low CD4 count was selected as having a significant impact on the occurrence of Kaposi's Disease [11]. Dicko et al also reported that our patient had a low CD4 count (240/mm 3 ) in an HIV-infected young boy with Kaposi [8]. On the other hand, a CD4 cell count ≥ 500 cells/mm 3 represents a lower risk of developing the disease [11].…”
Section: Discussionmentioning
confidence: 99%